Analisis Faktor yang Berhubungan Keikutsertaan Wanita Usia Subur Pada Skrining Kanker Serviks di Puskesmas Kota Selatan - Nur Khairun Nisa Adam; Irwan; Yasir Mokodompis (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Cervical cancer remains a global and national non-communicable health problem with a high incidence rate. Early detection through Visual Inspection with Acitic Acid screening is important for reducing morbidity and mortality, however, its coverage remains low. Globally, the participation rate of women of reproductive age screening is approximately 33,66%, while in Indonesia, it has not yet reached the 75% target. In Gorontalo Province, screening coverage is around 15 % and the Kota Selatan Community Health Center in 2025, only 1,77% of 2.039 women of reproductive age participated in screening. Low participation is influenced by several factors, including, knowledge, access to health services, access to information, husband’s support, and feelings of embarrassment. This study aims to analyze the factors associated with the participation of women in the Health Center. This quantitative study used an analytical survey with a Cross-sectional design and involved 55 respondents selected using Accidental sampling. Data were collected using questionnaires and analyzed using the Chi-square test. The result showed that access to information (p = 0.001) and feelings of embarrassment (p = 0.001), were associated with participation in cervical cancer screening, whereas knowledge (p = 0.664), access to health services (p = 0.080), and husband’s support (p = 0.512) were not. In conclusion, access to information and feelings and embarrassment are related to screening participation. Therefore, increased education and health services that ensure patient privacy are needed to improve the participation of women of reproductive age in cervical cancer screening.